Pola dan Urgensi Positivisasi Fatwa-Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia tentang Perbankan Syariah di Indonesia - Akhmad Faozan (Al-Manahij: Jurnal Kajian Hukum Islam, 2016)
This article examines the way and urgency of making fatwas of National Sharia Board of the Indonesian Ulama Council (DSN-MUI) on Islamic banking into a positive law in Indonesia. The background of this article is the fact that the only basis on the implementation of compliance with sharia principles in the operations of Islamic banking in Indonesia is a fatwa of DSN-MUI about Islamic banking. However, the fatwa position in the Indonesian legal system does not have a binding force for citizens included in the business activities of Islamic banking. This is because Indonesia is not an Islamic state, which makes the fatwa as a legal basis. Thus, making the fatwas of DSN-MUI about Islamic banking into a positive law is very urgent for the development of Islamic banking operations in Indonesia in order to have a strong legal foundation. The making of fatwa of DSN-MUI into a positive law is conducted by Central Bank of Indonesia (Bank Indonesia). Members of Islamic Banking Committee at Bank Indonesia along with the DSN-' MUI compose a draft of a regulation based on the fatwa and then it is submitted to the Governor of Bank Indonesia to be enacted as some of Bank Indonesia's regulations, for example Bank Indonesia's Regulation, Bank Indonesia's Circular Letter, or the Compilation of Sharia Banking Products and Services.